Sosialisasi Open Defecation Free (ODF) Sebagai Upaya Penguatan Komitmen Masyarakat Menuju Percepatan Desa Odf di Desa Jangur Kabupaten Probolinggo - Ajiputri, Adhiva Calista; Singal, Adeline Nathania Harini; Azizah, Dhiyaa Ummul; Soetikno, Fanny Amanda; Endah Mawarni, Roro Laksmi; Wahyudi, Kalvin Edo (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Open Defecation Free (ODF) is one of the conditions where a community is no longer practicing open defecation. The aim of the ODF socialization is to create an ODF Jangur Village and reduce the risk of disease due to an unclean and healthy environment. The community service activity carried out by KKNT 55 students at the East Java "Veteran" Development University was an activity aimed at strengthening community commitment towards accelerating the ODF village in Jangur Village. The target of this program is the people of Jangur Village who are still defecating in the river. The method used in this program consists of three stages of activity, namely the survey stage, updating the ODF map, and outreach. The results of this socialization activity are expected to increase the commitment of the Jangur village community to abandon their old habit of defecating in the river.